Visual impairment in urban school children of low-income families in Kolkata, India - Sambuddha Ghosh; Udayaditya Mukhopadhyay; Dipankar Maji; Gautam Bhaduri (Wolters Kluwer Medknow Publications, 2012)
To evaluate pattern of visual impairment in school children from low-income families in Kolkata, India, an institutional cross-sectional study was conducted among 2570 children of 10 primary schools. Ocular examination including refraction was done and pattern of visual impairment and refractive error was studied. The age range was 6-14 years. Refractive error was seen in 14.7%. Only 4 children were already wearing correction. Myopia and hypermetropia was present in 307 (11.9%) and 65 (2.5%) children, respectively. Visual acuity of less than 6/12 in better eye was present in 109 (4.2%) and 5 (0.2%) children pre- and post-correction, respectively. Eighteen children had amblyopia. Although prevalence of refractive error in this group is less compared to school children of all income categories reported from other cities of India, it is more compared to school children of all income categories from the same city. Refractive error mostly remains uncorrected in this group.